PTH-084 The use of budesonide in crohn's disease: a national population based study. (17th June 2017) - Chhaya, V; Alexakis, C; Saxena, S; Pollok, RC
Abstract : Introduction: The preparations of budesonide, Budenofalk and Entocort are licensed and recommended for the treatment of mild to moderate ileo-caecal Crohn's disease (CD) (1). Budesonide is advantageous in that systemic side effects are substantially reduced compared to conventional corticosteroids (CS). We hypothesised a reluctance to prescribe budesonide in the UK and aimed to compare the use of budesonide to overall CS use in CD. Method: We constructed an incident cohort of CD patients diagnosed between 1990–2009 using the Clinical Practice Research Datalink (CRPD), a validated national primary care research database. We extracted prescribing data for any prescription of oral steroid therapy following the formal diagnosis of CD. Budesonide users were defined as any patient with at least one prescription of this medication during follow-up. CS users were defined as any patient with at least one prescription for any oral steroid medication (budesonide included) during follow-up. We divided our cohort by date of CD diagnosis into five time periods to analyse prescribing trends for steroid subtypes: era 1 (1990–1993), era 2 (1994–1997), era 3 (1998–2001), era 4 (2002–2005) and era 5 (2006–2009). We performed Kaplan-Meier survival analysis for the first four time era to quantify the 5 year probability of receiving budesonide or any oral CS. Significance levels were compared using the log-rank test. Results: We identified 6997 patients with a diagnosis of CD. The median follow up time per patient was 4.2 years (IQR: 1.8–7.8). There were 474 (6.8%), 694 (9.9%), 1555 (22.2%), 2096 (30.0%) and 2178 (31.1%) incident cases in era 1, 2, 3, 4 and 5 respectively, reflecting the rising number of GP practices contributing to the database. A total of 4001 (57%) patients received a prescription for oral steroids within 5 years of diagnosis. Only 11.5% of patients with CD had received a prescription for budesonide within 5 years of diagnosis. The cumulative probability for receiving budesonide within 5 years was 0.8% (95%CI: 0.27%–2.5%), 11.5% (95%CI: 9.2%–14.4%), 12.6% (95%CI: 10.9%–14.5%), 10.6% (95%CI: 9.3%–12.1%), for era 1, 2, 3 and 4 respectively (log-rank p<0.001). The cumulative probability for receiving oral steroids within 5 years was 39.6% (95%CI: 34.8%–44.9%), 49.3% (95%CI: 44.9%–53.9%), 51.0% (95%CI: 48.1%–54.0%), 52.2% (95%CI: 49.6%–54.9%), for era 1, 2, 3 and 4 respectively (log-rank p<0.001). Conclusion: Our findings demonstrate a potential underuse of budesonide in patients with CD, despite strong recommendations in guidelines for its use as a first line agent in mild to moderate ileo-caecal CD. Clinical guidelines should be reinforced at a primary care level to ensure wider use of budesonide over traditional oral CS treatment. Reference: . Dignass, et al. J Crohns Colitis2010Feb;4(1):28–62 Disclosure of Interest: None Declared